Community Empowerment as a Catalyst for Marine Ecotourism: The Case of Spermonde Archipelago, Makassar - Prakasa, Yudha; Sawu, Michael Rudolfus; Ulinnuha, M. Farid (Goodwood Publishing, 2025)
Purpose: This study aimed to examine the development of marine ecotourism and the community’s participation in marine ecotourism development in the Spermonde Archipelago. The findings were used as a foundation to create a conceptual framework for community empowerment in marine ecotourism in the Spermonde Archipelago. Methodology/Approach: The research was conducted on several islands in the Spermonde Archipelago, Makassar City, including Samalona Island, Kodingareng Keke Island, Barrang Caddi Island, and Lanjukang Island. The study employed a qualitative approach with a case study method. Data were collected through interviews, observations, documentation, and a literature review. The informants included local communities, government officials, the private sector, and academics. The data were analyzed using qualitative thematic analysis. Results/Findings: The research developed a framework for community empowerment in marine ecotourism, focusing on improving political, economic, and environmental quality of life. Based on findings from the Spermonde Archipelago, it showed that ecotourism transformed natural resources into tourism products, leading to diverse community perceptions about its impacts. Community involvement was driven by economic motives but limited by knowledge and skills in integrating tourism and conservation. Nonetheless, communities had opportunities to participate in development, planning, and benefit distribution. Limitations: This research did not provide a detailed set of practical strategies based on the formulated community empowerment model. Contribution: This study contributed to the conceptual understanding by proposing a community empowerment model in the Spermonde Archipelago. This model was expected to serve as a theoretical reference for implementing community empowerment focused on social and environmental justice.